Utilization of Used Materials to Increase Early Childhood Art Creativity in Flamboyan Kindergarten - Nur Istiana Makarau; Hibana; Susilo Surahman (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2022)
Early childhood is the basis for instilling life values ​​in order to become creative and innovative human beings and have skills, one of which is by utilizing used materials in a learning activity at school. The purpose of this study was to find out more about the use of used materials as a medium to increase artistic creativity in early childhood in Flamboyan Kindergarten. This study uses a qualitative research method with a qualitative descriptive approach. Observation, interview, and documentation are data collection techniques. While the data analysis techniques include data reduction, data presentation, and drawing concluding. The results showed that the use of used materials can increase artistic creativity in Kindergarten Flamboyan which is used as teaching material by paying attention to aspects of child development. This is evidenced by the children exploring and creating works from used materials accompanied by their homeroom teacher.